Cardiac Remodeling During Pregnancy With Metabolic Syndrome: Prologue of Pathological Remodeling. Issue 7 (16th February 2021) - Yang, Yijun; Kurian, Justin; Schena, Giana; Johnson, Jaslyn; Kubo, Hajime; Travers, Joshua G.; Kang, Chunya; Lucchese, Anna Maria; Eaton, Deborah M.; Lv, Maoting; Li, Na; Leynes, Lorianna G.; et al.
Abstract : Background: The heart undergoes physiological hypertrophy during pregnancy in healthy individuals. Metabolic syndrome (MetS) is now prevalent in women of child-bearing age and might add risks of adverse cardiovascular events during pregnancy. The present study asks if cardiac remodeling during pregnancy in obese individuals with MetS is abnormal and whether this predisposes them to a higher risk for cardiovascular disorders. Methods: The idea that MetS induces pathological cardiac remodeling during pregnancy was studied in a long-term (15 weeks) Western diet–feeding animal model that recapitulated features of human MetS. Pregnant female mice with Western diet (45% kcal fat)–induced MetS were compared with pregnant and nonpregnant females fed a control diet (10% kcal fat). Results: Pregnant mice fed a Western diet had increased heart mass and exhibited key features of pathological hypertrophy, including fibrosis and upregulation of fetal genes associated with pathological hypertrophy. Hearts from pregnant animals with WD-induced MetS had a distinct gene expression profile that could underlie their pathological remodeling. Concurrently, pregnant female mice with MetS showed more severe cardiac hypertrophy and exacerbated cardiac dysfunction when challenged with angiotensin II/phenylephrine infusion after delivery. Conclusions: These results suggest that preexisting MetS could disrupt physiological hypertrophy during pregnancy to produce pathological cardiac remodeling that could predispose the heart to chronic disorders. Abstract : Supplemental Digital Content is available in the text.